Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2174/1874944501912010086
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and Clinical Performance of Nurses Initiated and Management of Antiretroviral Therapy: Narrative Review

Abstract: Introduction: Self-efficacy plays a major role in the behaviour of a human being by how he/she approaches a goal, task or a challenge so that a desired level of performance is produced. The objective of this paper is to review and analyse literature on self-efficacy and clinical performance among professional nurses regarding quality of care in implementation of NIMART programme. Methodology: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It can be assumed that SE has a significant influence on the use of considered STI-protective behaviors because of the significant correlation coefficients of each regression analysis. Previous studies support this association in terms of each listed STI-protective behavior (Baele et al 2001;Golub et al 2019;Ma et al 2006;Mangi et al 2019;Martin-Smith et al 2018;Mateske et al 2013;Petrovic et al 2011). Rank correlations describe correlations between knowledge and realization of STI vaccinations, STI tests, and ART.…”
Section: Discussionmentioning
confidence: 82%
“…It can be assumed that SE has a significant influence on the use of considered STI-protective behaviors because of the significant correlation coefficients of each regression analysis. Previous studies support this association in terms of each listed STI-protective behavior (Baele et al 2001;Golub et al 2019;Ma et al 2006;Mangi et al 2019;Martin-Smith et al 2018;Mateske et al 2013;Petrovic et al 2011). Rank correlations describe correlations between knowledge and realization of STI vaccinations, STI tests, and ART.…”
Section: Discussionmentioning
confidence: 82%
“…Inadequate or non-standardised training and the lack of continuous clinical mentoring and supervision by clinic managers were mentioned in most studies as barriers to the implementation of NIMART. 19 , 20 , 23 , 24 , 25 , 27 , 28 , 35 , 36 , 37 …”
Section: Resultsmentioning
confidence: 99%
“…Inadequate or non-standardised training and the lack of continuous clinical mentoring and supervision by clinic managers were mentioned in most studies as barriers to the implementation of NIMART. 19,20,23,24,25,27,28,35,36,37 As mentioned before, NIMART training was, and is being conducted by various NGOs, the NDoH and private training providers. One of the challenges is that training is not standardised, ranging from a few days to a few weeks or even months, which makes it difficult to evaluate its effectiveness or quality.…”
Section: Non-standardised Training and Inadequate Mentoringmentioning
confidence: 99%
“…8 One such study conducted in the Eastern Cape province of South Africa found satisfactory self-efficacy in the clinical performance of NIMART amongst 358 trained nurses, with some limitations in their abilities regarding clinical evaluation. 9 Care provided by providers with low levels of self-rated expertise who treat low numbers of HIV and AIDS patients tends to lead to less favourable patient outcomes. 10…”
Section: Introductionmentioning
confidence: 99%